Neural correlates of the abolished self-referential memory effect in schizophrenia. Issue 3 (31st May 2013) - Zhao, Y.; Zhang, D.; Tan, S.; Song, C.; Cui, J.; Fan, F.; Zhu, X.; Zou, Y.; Luo, Y.
Abstract : Background: The self-referential memory (SRM) effect refers to the phenomenon that stimuli processed with reference to the self are better remembered than those referenced to others. Studies have shown that schizophrenia patients do not have this memorial advantage for self-referenced information. The current study investigated the electrophysiological mechanism of the abolished SRM effect in schizophrenia. Method: Twenty schizophrenia patients and 22 controls were recruited to complete an SRM task. We used a high-time resolution event-related potential (ERP) technique to analyze the electrophysiological differences between patients and controls during self- and other-reflection processing. Results: Behavior data indicated that healthy controls had a typical SRM bias that was absent in the schizophrenia patients. ERP comparison between groups showed that the schizophrenia patients presented smaller voltages in both self- and other-reflection conditions in the 160–260 ms (P2 component) and 800–1200 ms (positive slow wave) time windows over the pre/frontal cortex. Furthermore, the N2 amplitudes (270–380 ms) differed between self- and other-reflection conditions in patients but not in normal controls. More importantly, we found that the P3 amplitudes in the parietal cortex correlated significantly with the SRM bias score in the patients ( r = –0.688). Conclusions: These results provide comprehensive and direct electrophysiological evidence for self- and other-reflective dysfunction in schizophrenia patients and contribute to our understanding of the underlying neural substrates of the abolished SRM effect in schizophrenia.